Analytical electrochemistry - Wang, Joseph (Wiley-VCH, 2006)
Includes bibliographical references and index; Fundamental concepts -- Study of electrode reactions and interfacial properties -- Controlled-potential techniques -- Practical considerations -- Potentiometry -- Electrochemical sensors